Kapitaal en arbeid. - Marx, Karl; Domela Nieuwenhuis, Ferdinand ('s Hage : Liebers, 1881)
Collectie Vrijzinnige Werkmansbibliotheek
Nederlands
Monografie
Keywords: Vrijzinnige Werkmansbibliotheek; marxisme